(untitled) (Nepalese Journal of Radiology, 2012)
Aim: 1. To assess relationship between fetal foot length and gestation age and develop a nomogram. 2. To assess relationship between fetal foot length and femur length. Meterials and Method: Cross sectional study. Fetal foot length was taken from the skin edge overlying calcaneus to the distal end of the longest toe on either plantar or the sagittal view in 860 singleton pregnant women between 15 and 40 weeks’ gestation. Normal case was defined as normal sonographic findings during examination and normal infant examination at birth or both. Final study population constituted 779 healthy fetuses. The relationship between gestational age to foot length was analyzed by simple linear regression. Correlation of fetal foot length with gestational age and femur length were also obtained. Results: A nomogram for fetal foot length was obtained. There is linear relationship between foot length and gestational age [foot length (mm)=2.494xGestational age (weeks)-15.46] with significant correlation (r=0.970 and p=0.000) and between foot length and femur length [foot length(mm)=1.049xfemur length (mm)+0.648] with significant correlation (r=0.980 and P=0.000). Femur length/ Foot Length ratio was 0.9 and 1.0 in most of the cases. Conclusion: Nomogram was obtained for fetal foot length at various gestational ages in our population. There is linear relationship and good correlation between foot length and gestational age and foot length and femur length. Fetal foot length can be used as an alternative fetal parameter to assess gestational age. Femur length/ Foot Length ratio is fairly constant throughout gestation. DOI: http://dx.doi.org/10.3126/njr.v1i1.6317 Nepalese Journal of Radiology Vol.1(1): 15-22